2015
DOI: 10.1136/bjophthalmol-2015-307099
|View full text |Cite
|
Sign up to set email alerts
|

En face mode of swept-source optical coherence tomography in circumscribed choroidal haemangioma

Abstract: En face SS-OCT is a rapid, non-invasive, high-resolution, technology, which allows a complementary study to cross-sectional scans in CCH. A characteristic multilobular pattern, with a hyper-reflective halo surrounding the tumour, was found in en face SS-OCT images. No morphological differences were found between naïve patients and patients who received previous treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, diagnosis can be challenging when the presentation of these tumors is atypical, and new imaging modalities on OCT such as swept source and OCT angiography can offer a helpful auxiliary tool in such cases [16, 17, 22]. To the best of our knowledge, this is the largest study describing SD-OCT features in untreated cases of CCH and the first to investigate associated ODR measurements of SRF in the diagnosis of this pathology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, diagnosis can be challenging when the presentation of these tumors is atypical, and new imaging modalities on OCT such as swept source and OCT angiography can offer a helpful auxiliary tool in such cases [16, 17, 22]. To the best of our knowledge, this is the largest study describing SD-OCT features in untreated cases of CCH and the first to investigate associated ODR measurements of SRF in the diagnosis of this pathology.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, the ODR can offer an auxiliary tool for the differential diagnosis of those cases, while new imaging OCT modalities might add further information about the internal composition of CCH. A recent study of 22 previously treated cases of CCH that had been imaged by swept-source OCT described a multilobular pattern with hyporeflective, confluent areas corresponding with the lumen of the tumor vascular spaces [22]. Another recent study showed that OCT-A can detect blood flow patterns in CCH [28].…”
Section: Discussionmentioning
confidence: 99%
“…4 SS-OCT has recently been proposed as a beneficial imaging modality to more accurately measure the size of the tumor in comparison with ultrasonography 7 and to provide a distinct multi-lobular, sponge-like pattern with a hyperreflective halo surrounding the tumor. 8 OCTA is a noninvasive imaging modality capable of acquiring 3-D retinal and choroidal microvascular maps without the use of exogenous dye. It also provides information about vascular flow in various diseases including vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multiple authors report imaging modalities used to evaluate choroidal hemangiomas, with variable advantages. 4,[6][7][8] Given the location and vascularized nature of these tumors, it is difficult to ascertain with traditional imaging the depth and size, underlining the need for further imaging modalities to better evaluate this tumor. To date, findings from optical coherence tomography angiography (OCTA) have yet to be reported for a choroidal hemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is often suspected clinically, and multimodal imaging is considered to be useful for the differential diagnosis of CCH from other malignant tumors such as melanoma [8][9][10]. On uorescein angiography (FA), exudative CCH appears varying degrees of hyper uorescence in all phases [1].…”
Section: Introductionmentioning
confidence: 99%